The ERK1/2 pathway regulates testosterone synthesis by coordinately regulating the expression of steroidogenic enzymes in Leydig cells - Matzkin, Maria Eugenia (2013)
Adult mice with a Leydig cell specific deletion of MAPK kinase (MEK) 1 and 2 (Mek1(f)(/)(f);Mek2(-/-);Cre(+)) mice display Leydig cell hypoplasia and hypergonadotropic hypogonadism. We used radioimmunoassays and quantitative PCR to evaluate the function and expression of the Leydig cell genes involved in the conversion of cholesterol to testosterone (Star, Cyp11a1, Hsd3b6, Cyp17a1 and Hsd17b3), androgen metabolism (Srda1 and Dhrs9), and four transcription factors (Creb1, Nr5a1, Nr4a1 and Nr0b1) that regulate the expression of steroidogenic genes. We show that Star, Hsd3b6, Cyp17a1 and Hsd17b3 are downregulated in Ledyig cells of adult Mek1(f)(/)(f);Mek2(-/-);Cre(+) mice whereas Srda1 and Dhrs9 are upregulated and Creb1, Nr5a1, Nr4a1 and Nr0b1 are unchanged or upregulated. Functionally, all the downregulated genes but none of the upregulated genes contribute to the decrease in testosterone synthesis in Leydig cells of adult Mek1(f)(/)(f);Mek2(-/-);Cre(+) mice because they produce low testosterone and dihydrotestosterone when stimulated with hCG or when incubated with testosterone precursors such as progesterone or androstenedione.